The Movement of the Spirit Around the World in Pentecostalism - Onyinah, Opoku (Transformation, 2013)
The article makes a brief survey of the movement of the Holy Spirit in various church traditions across the world. It begins by highlighting the various revivals in Christianity, including Pietism among Lutheranism and the Holiness movement. It shows these as the precursors to the emergence of Pentecostalism in the 20th century. The Latter Rain movement, which came out of the Pentecostal movement, is analysed as a contributing factor to the Charismatic renewal within world Christianity. The empowerment of the Holy Spirit, which is one of the distinctive emphases of the Charismatic renewal, is shown as providing the opportunity to build the kingdom of the Lord, by various denominations, in love and unity.